Safety, tolerability, and pharmacokinetics of single and multiple ascending Oral doses of DA‐8010 in healthy subjects: First‐in‐human phase I study - Dae Young Lee; Min Jung Lee; Chaelim Ryu; Heewon Lee; Ashley Brooks (Wiley, 2023)
Abstract This study assessed the safety, tolerability, and pharmacokinetics of single and multiple oral doses of DA‐8010, a muscarinic M3 receptor antagonist, in healthy subjects. This was a randomized, double‐blind, placebo‐controlled, ascending single (Part A: 1, 2.5, 5, 20, and 40 mg QD fasted and 10 mg QD fasted and fed) and multiple doses (Part B: 5, 10, and 20 mg QD from Days 1 to 7 fasted), sequential‐group study. Safety data were analyzed descriptively, time to maximum plasma concentration (tmax) nonparametrically, and pharmacokinetic parameters using power and mixed models and ANOVA. Of 109 subjects randomized (Part A = 69 and Part B = 40; each part consisted a female group), 31 (44.9%) in Part A and 29 (72.5%) in Part B experienced treatment‐emergent adverse events (TEAEs) in a dose‐related manner. Common drug‐related TEAEs in Part A and B were dizziness (8.7% and 15.0%), headache (5.8% and 12.5%) and blurred vision (8.7% and 20%). One male (20 mg) and one female (10 mg) from Part B discontinued the study due to a confusional state, and nausea and vomiting. Irrespective of sex, DA‐8010 was steadily absorbed following single and multiple doses in the fasted state with increased systemic exposure in a dose‐proportional manner with maximum plasma concentration occurring at a median tmax between 4.0 and 6.0 h. A high‐fat meal increased systemic exposure. DA‐8010 was safe, well tolerated, and well absorbed at lower doses and moderately tolerated at higher doses without any notable effects of food and sex.